Penerapan Metode Vikor dalam Pemilihan Bibit Unggul Pohon Karet - Rizki Ananda Putra Fajar; Rakhmat Kurniawan; Sriani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Rubber plant is one of the plantation commodities that has an important role in economic activities in Indonesia. The need for rubber seeds continues to increase in line with the increase in the area of ​​smallholder rubber plantations and the government. Quality seeds are a community need in developing rubber plantations in Indonesia from year to year. The first step to get good rubber seeds is that rubber farmers need to use quality rubber seed planting material and are able to produce high latex. Given the very importance of seeds in determining quality rubber repair. With a Decision Support System with the vikor method to build a system that has the ability to be able to assist farmers in choosing superior rubber tree seeds with a system that is able to provide problem solving skills and communication skills for problems with semi-structured and unstructured conditions. This study uses the vikor method because this method is suitable for use in most real-time problems such as making decisions to find quality rubber tree seeds so that this research can be useful for rubber tree farmers in improving the quality of superior seeds.